2019
DOI: 10.1007/s11425-018-9500-x
|View full text |Cite
|
Sign up to set email alerts
|

On the polynomiality and asymptotics of moments of sizes for random (n, dn ± 1)-core partitions with distinct parts

Abstract: Amdeberhan's conjectures on the enumeration, the average size, and the largest size of (n, n + 1)-core partitions with distinct parts have motivated many research on this topic. Recently, Straub and Nath-Sellers obtained formulas for the numbers of (n, dn−1) and (n, dn+1)-core partitions with distinct parts, respectively. Let X s,t be the size of a uniform random (s, t)-core partition with distinct parts when s and t are coprime to each other. Some explicit formulas for the k-th moments] were given by Zaleski … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
(76 reference statements)
0
1
0
Order By: Relevance
“…Also, simultaneous core partitions are connected with Motzkin paths and Dyck paths (see [9,11,39,40]). Some statistics of simultaneous core partitions, such as numbers of partitions, numbers of corners, largest sizes and average sizes, have attracted much attention in the past twenty years (see [2,3,4,7,8,10,13,14,15,18,20,21,23,24,25,29,31,33,35,37,42,43,44]). For example, Anderson [3] showed that the number of (s 1 , s 2 )-core partitions is equal to 1 s 1 +s 2 s 1 +s 2 s 1…”
Section: Introductionmentioning
confidence: 99%
“…Also, simultaneous core partitions are connected with Motzkin paths and Dyck paths (see [9,11,39,40]). Some statistics of simultaneous core partitions, such as numbers of partitions, numbers of corners, largest sizes and average sizes, have attracted much attention in the past twenty years (see [2,3,4,7,8,10,13,14,15,18,20,21,23,24,25,29,31,33,35,37,42,43,44]). For example, Anderson [3] showed that the number of (s 1 , s 2 )-core partitions is equal to 1 s 1 +s 2 s 1 +s 2 s 1…”
Section: Introductionmentioning
confidence: 99%